Advances in the Biological Removal of Sulphides from Aqueous Phase in Anaerobic Processes: A Review - Huilinir-Curio, C; Montalvo-Martinez, S (Canadian Science Publishing, 2015)
In this paper, we review the latest developments in biological methods used in the removal of hydrogen sulphide, present in the liquid phase in anaerobic reactors. The toxicity of H2S to methane-forming microorganisms and the problems caused by the presence of this compound in the biogas generated during this process, as well as the main causes of hydrogen sulphide generation in anaerobic processes of wastes are also reviewed. We especially discuss the fundamentals in applying micro-aerobic conditions to remove dissolved hydrogen sulphide from the aqueous phase of an anaerobic reactor. The alternative technology of simultaneous removal of sulphide, nitrate, and organic matter is under recent investigation. Therefore, this review paper includes a study and analysis of the microbiological basis of this technology, the physical and chemical factors that influence the process and the potential application of this technology on different types of wastewaters and situations. Also considered are the fundamentals of both biofilm reactors and microbial fuel cells desulphurization. Because relatively few studies on modeling desulphurisation processes are available, we discuss the advances made in that area. © 2016 Published by NRC Research Press.